2016
DOI: 10.1007/s00405-016-3941-5
|View full text |Cite
|
Sign up to set email alerts
|

Bone-anchored hearing aids in conductive and mixed hearing losses: why do patients reject them?

Abstract: This study aimed to report the bone-anchored hearing aid uptake rate and the reasons for their rejection by patients with conductive and mixed hearing losses. A retrospective review was performed of 113 consecutive patients with unilateral or bilateral conductive or mixed hearing loss referred to the Greater Manchester bone-anchored hearing aid (BAHA) programme between September 2008 and August 2011. 98 (86.7 %) patients were deemed audiologically suitable for BAHA implantation. Of these, 38 (38.8 %) had BAHA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 24 publications
3
16
0
Order By: Relevance
“…Regarding the first of these potential issues, we believe that a new wearing option can be of substantial importance for current and future patients, if it is perceived as attractive by the users. It is known that a significant number of patients chooses not to use or to discontinue the use of bone conduction devices because either a surgical intervention is needed or the nonsurgical wearing option is not aesthetically appealing [ 7 , 24 , 25 ]. It is therefore not surprising that at least one other manufacturer has presented a new nonsurgical alternative to implantable bone conduction devices recently [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the first of these potential issues, we believe that a new wearing option can be of substantial importance for current and future patients, if it is perceived as attractive by the users. It is known that a significant number of patients chooses not to use or to discontinue the use of bone conduction devices because either a surgical intervention is needed or the nonsurgical wearing option is not aesthetically appealing [ 7 , 24 , 25 ]. It is therefore not surprising that at least one other manufacturer has presented a new nonsurgical alternative to implantable bone conduction devices recently [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Siau et al . reported that 30 per cent of patients who were eligible for a BAHA rejected BAHA implantation because of cosmetic concerns, including the size of the abutment and subsequent hair loss 12 …”
Section: Introductionmentioning
confidence: 99%
“…In a study of BAHA-eligible patients with conductive and mixed hearing loss, similar findings were reported: 38 (39 per cent) accepted implantation and 60 (61 per cent) declined. When the sample was divided into patients with unilateral or bilateral hearing problems, acceptance rates were 64.2 per cent ( n = 27) and 19.6 per cent ( n = 11) respectively 6 …”
Section: Resultsmentioning
confidence: 99%
“…In another study of a conductive and mixed hearing loss sample, Siau et al . found the most common reasons for rejection to be anxiety about the surgery (reported by 27 patients; 45 per cent), cosmetic concerns ( n = 18; 30 per cent) and insufficient benefit during a softband trial ( n = 16; 27 per cent) 6 . While Siau and colleagues provide some indication of the reasons for declining, neither study was specifically designed to explore the reasons for refusal: instead, these were gleaned from clinical notes.…”
Section: Resultsmentioning
confidence: 99%